Cone Beam Computed Tomography Detection of Extracranial Vertebral Artery (EVA) Calcification and Ectasia - Steven Richard Singer; Mel Mupparapu (Wolters Kluwer Medknow Publications, 2019)
Carotid artery calcification is frequently noted in panoramic dental radiographs but more evident on cone beam computed tomography (CBCT) examinations. Vertebral artery calcification and ectasia, although rare, can place the patient for equal risk for a cerebrovascular accident (stroke). The aim of this article is to radiographically identify calcified atheromatous plaque, as well as, atresia related to vertebral artery in large field of view CBCT examinations. This article presents two patients with radiographic diagnosis of vertebral artery disease. In case 1, the large field of view CBCT volume was obtained for evaluation of the temporomandibular joints. A curvilinear high-density structure was seen within the left transverse foramen of C3. Based on the density, location, and shape, a radiographic diagnosis of calcified atheromatous plaque was made. The patient was referred to her physician for management. In case 2, irregularly shaped, small, high-density structures were noted on the CBCT examination close to the left carotid bifurcation at the level of C3-C4. It was also noted that the left transverse foramen of C4 was enlarged. A diagnosis of calcified atheroma of left carotid was made in patient 1, and calcified atheromatous plaque in the left carotid bifurcation area and concomitant vertebral artery ectasia was made in patient 2. Both the patients were referred to their physicians for management. Although prevalence of carotid artery stenosis and calcification is noted more frequently in CBCT examinations, vertebral artery calcification or ectasia is rare but because of its potential risk for causation of stroke, identification is paramount.